Зовнішньоторговельна діяльність України з ЄС в кризовий та посткризовий періоди - Зайцев, В.Є.; Малюта, І.А.; Трунова, А.Д. (Культура народов Причерноморья, 2013)
Проаналізовані результати зовнішньоторговельної діяльності України з країнами ЄС.
Надана характеристика особливостей такого співробітництва в період світової економічної кризи та в
посткризовий період. Розраховані відповідні показники. Запропоновані заходи, що сприятимуть
поглибленню співпраці.
Ключові слова: Зовнішня торгівля, експорт, імпорт, структура торгівлі, сальдо, індекс
компліментарності. Проанализированы результаты внешнеторговой деятельности Украины со странами ЕС.
Дана характеристика особенностей такого сотрудничества в период мирового экономического кризиса
и в посткризисный период. Рассчитаны соответствующие показатели. Предложены мероприятия,
которые будут способствовать углублению сотрудничества.
Ключевые слова: Внешняя торговля, экспорт, импорт, структура торговли, сальдо, индекс
комплиментарности. At the current stage of development Ukrainian State is highly integrated into the international
economy and has international trade relations with more than 200 countries of the world. At present time the
European Union is one of the most important trading partners of our country.
This article presents the results of international trade activity of Ukraine with the EU countries. Trade relations
with European Union are analyzed within the context of long term consequences of the world economic and
financial crisis, which caused significant changes in the development of economic cooperation between Ukraine
and EU. The article characterizes peculiarities of this cooperation during the active phase of the world
economic crisis and in the post-crisis period.
The article provides a detailed analysis of the volume of trade between Ukraine and its main trading partners
within EU, i.e. Germany, Poland, Italy, Hungary. It contains data, which characterizes peculiarities of the
commodity structure of exports and imports. It also proves existence of asymmetry in trade relations between
Ukraine and EU.
The article pays particular attention to the problem of conformity between foreign trade structure of EU and that
of Ukraine by calculating relevant trade conformity indices. Calculation results show high level of international
trade conformity between Ukrainian exports and EU imports. However, the index value obtained from the
analysis of conformity between EU exports and Ukrainian imports has even higher value.
The article suggests measures, which would stimulate international economic cooperation between Ukraine and
EU.
Keywords: Foreign trade, export, import, trade structure, balance, complementary index.